Global crop impacts, yield losses and action thresholds for fall armyworm (Spodoptera frugiperda): A review. (July 2021) - Overton, Kathy; Maino, James L.; Day, Roger; Umina, Paul A.; Bett, Bosibori; Carnovale, Daniela; Ekesi, Sunday; Meagher, Robert; Reynolds, Olivia L.
Abstract: The fall armyworm (FAW), Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae), is a highly polyphagous plant pest that can severely impact yields of several agricultural crops. Understanding the economic impact and management thresholds for FAW across a variety of crop commodities is crucial for effective management. Evaluating the peer-reviewed and grey literature, we compiled global data on: (1) yield losses reported as a result of FAW infestations, (2) the relationship between FAW pressure/density and reported yield loss, and (3) current known economic injury levels, economic thresholds and action thresholds. We identified 71 references that reported yield losses from FAW infestation, with a total of 888 separate yield loss entries. The majority of research quantifying yield losses and the relationship between pest pressure and yield has focused on maize, sorghum, and cotton, with some evidence for sweet corn, bermudagrass, and rice. Yield loss varied between management strategies, with genetically modified and/or insecticide treated crops typically retaining higher yields. Most studies investigating the relationship between FAW density and yield loss across different crops have focused on early and mid FAW larval instars and on vegetative through to reproductive plant growth stages, with minimal research on both late larval instars and on plant seedlings. Economic thresholds were not reported in the literature. The reporting of economic injury levels and action thresholds varied significantly both between and within crops, highlighting the need for a standardised approach when measuring FAW pressures or densities that elicit management responses. Highlights: We conducted reviews to present yield loss impacts and management thresholds for FAW. Across all crops, reported yield losses varied depending on management strategies. Quantifying yield loss is more valuable in threshold development than damage ratings. Standardising pest pressure is difficult due to inconsistent metrics reported in the literature.